Materiales para el estudio de la piedad popular fenicio-púnica en la Península Ibérica: la antroponimia - Vidal, Jordi ('Ilu. Revista de Ciencias de las Religiones, 2003)
Anthroponimy has traditionally been regarded as the main approach to knowledge about popular piety in the field of the Ancient Near Eastern studies. However, several problems related to the use of this kind of material limit its potential. In this work besides the compilation of Phoenician and Punic anthroponimy found in the Iberian Peninsula, a contextualization in the framework of Canaanite religion in the 1st millennium and its expansion the Western Mediterranean has been attempted.
Keywords: Anthroponomy; Phoenician; Punic; Iberian peninsula